MIGRAIN DENGAN AURA: TINJAUAN PUSTAKA - Oktarlina, Rasmi Zakiah; Setiawan, Muhamad Rizky; Karima, Nisa; Sutarto, Sutarto (CV. Jasa Sukses Abadi, 2025)
Migraine is a neurovascular disorder characterized by recurrent headaches with symptoms such as nausea, phonophobia and photophobia. Factors related to migraine include food, psychosocial and environmental factors. The purpose of this article is to identify migraine trigger factors. The type of research is a literature review. Migraines can occur due to trigger factors including foods with certain ingredients (such as tyramine, chocolate), menstrual cycle, weather, sleep patterns, bright light, and screen time. The prevalence of migraine in the world reaches 10-14% with the highest incidence in North America, Central America and South America. In Indonesia alone, the prevalence of migraine has reached 3.5 million people with the highest coming from individuals aged 15-24 years. Until now, the exact cause of migraines is not known. However, there are many risk factors that can influence the occurrence of migraines. The diagnosis of migraine can be made through the results of the history and physical examination, and if necessary, supporting examinations can also be carried out to rule out other secondary causes that may influence migraine. Efforts to prevent migraines from occurring by controlling and avoiding trigger factors and living a healthy lifestyle. Migraine prevention can be done by avoiding trigger factors and adopting a healthy lifestyle, such as maintaining a regular sleep pattern, managing stress, and consuming a balanced nutritious diet.